Management of a Community Nursing–Based Healthy Workplace Program for Enhancing the Productivity and Well-Being of Elderly Workers - Cicci Chairunisa Mas’um; Rismanudin; Sri Ayu Nuramalia Kaharuddin; Ambo Anto; Geovanny Serviam Permana Putri Rahamitu; Andi Yani Indra Dewi; Andi Haryati Hasrib (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2026)
The increasing participation of older adults in the workforce has emphasized the need for workplace health programs that support productivity and well-being. Elderly workers often experience age-related challenges, including chronic diseases, fatigue, and psychosocial problems that may affect their work performance and quality of life. This study aimed to develop and evaluate a community nursing-based Healthy Workplace program for elderly workers in South Sulawesi, Indonesia. A Research and Development (R&D) approach was applied through needs assessment, program design, validation, implementation, and evaluation stages. Data were collected using interviews, observations, questionnaires, focus group discussions, and document reviews. The program included occupational health education, ergonomic counseling, psychosocial support, physical activity promotion, and regular health monitoring. The findings showed improvements in occupational health knowledge, workplace safety practices, productivity, and physical and psychological well-being among participants. Collaboration among community nurses, employers, workers, and local health services also strengthened program sustainability. The Healthy Workplace program offers a practical strategy to promote healthy aging and improve the quality of life of elderly workers.